2015
DOI: 10.1590/1414-431x20144298
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pathogenicity of Coxsackievirus A16 circulating and noncirculating strains in vitro and in a neonatal mouse model

Abstract: An enterovirus 71 (EV71) vaccine for the prevention of hand, foot, and mouth disease (HMFD) is available, but it is not known whether the EV71 vaccine cross-protects against Coxsackievirus (CV) infection. Furthermore, although an inactivated circulating CVA16 Changchun 024 (CC024) strain vaccine candidate is effective in newborn mice, the CC024 strain causes severe lesions in muscle and lung tissues. Therefore, an effective CV vaccine with improved pathogenic safety is needed. The aim of this study was to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…VP1, VP2, and VP3 capsid proteins are exposed on the viral surface, while VP4 is usually situated on the inner portion. There are many B-lymphocyte antigenic epitopes and virulence-associated sites in the viral structural proteins [26][27][28][29][30]. Investigations into the geographical distribution and genetic characteristics of the gene in the P1 coding region of CVA16 associated with HFMD in China may provide basic information for the prevention and control of HFMD.…”
Section: Introductionmentioning
confidence: 99%
“…VP1, VP2, and VP3 capsid proteins are exposed on the viral surface, while VP4 is usually situated on the inner portion. There are many B-lymphocyte antigenic epitopes and virulence-associated sites in the viral structural proteins [26][27][28][29][30]. Investigations into the geographical distribution and genetic characteristics of the gene in the P1 coding region of CVA16 associated with HFMD in China may provide basic information for the prevention and control of HFMD.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical signs appeared in ICR mice showed weight loss, difficulty in movement, hunched posture, and limb paralysis. The severity of the clinical disease was scored as 0: healthy; 1: lethargy and inactivity; 2: wasting; 3: limb shaking weakness; 4: hind limb paralysis, and 5: moribund/dead . The limb paralysis was found on day 5 of PID.…”
Section: Resultsmentioning
confidence: 99%
“…To understand the susceptibility of mice strains to CVA-16/311 virus, Swiss albino and ICR (Institute of Cancer Research) mice strains were selected. 19 In the study, comparison to check the susceptibility of different mice strains which include ICR mice and Swiss albino for CVA-16/311 infection was conducted. It was observed that as compared to Swiss albino, ICR mice are more susceptible to CVA-16/ 311 infection.…”
Section: Susceptibility Of Mice Strains and Inoculation Of Cva-16 Vmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, readily discernible pathological changes were detected in both brain and myocardial tissue. Compared with enterovirus species A virus infection models, including EV-A71 ( Dong et al, 2016 ; Yue et al, 2016 ), CV-A16 ( Huang et al, 2015 ; Mao et al, 2012 ), CV-A6 ( Zhang et al, 2017b ), and CV-A10 ( Zhang et al, 2017a ), which are associated with hind limb paralysis and/or severe respiratory involvement, the enterovirus species B CV-B4 had comparably minor pathology in skeletal muscle and lung tissue.…”
Section: Discussionmentioning
confidence: 97%